Factors driving large-scale adoption of sustainable intensification practices in the Indo-Gangetic Plain (Cereal Systems Initiative for South Asia - CSISA) - CGIAR Research Program on Wheat (2018)
Research by the CIMMYT-led Cereal Systems Initiative for South Asia (CSISA) under WHEAT and RICE identified proven factors and business models that positively impacted farmers’ adoption of sustainable intensification and climate smart farming practices. These findings and pilots built on them, when scaled up, help government agencies prioritize the portfolio of climate smart agricultural practices that can maximize crop productivity, profitability and input use efficiency, while improving farmer capacity and reducing the environmental footprint.